Sales and Operations Planning (S&OP) and Digital Transformation: A Narrative Review (Research, Society and Development, 2020)
This article discusses the concept of Digital Transformation related with Sales and Operations Planning (S&OP) and how it can benefit the business. That link vision is a relatively new concept in the field of business research initiative, and much work remains to be done to establish it. The methodology used was the narrative review that identifies what was written about a topic or topic. The complexity aspects that appear in the S&OP are getting 'clean' data from company business systems to feed the process. After a general overview of the evolution of the studies on Digital Transformation and S&OP, the relationship of the object of analysis of this review to the business was verified. Finally, the article provides a brief introduction to Digital Transformation and focuses on the reasons and advantages for S&OP process.